HASIL SENI BANGUN BERGAYA INDIS: STUDI KASUS KELESTARIAN SEJUMLAH BENTENG DI JAWA TENGAH - Novida Abbas (Berkala Arkeologi, 1998)
The study of the preservation of the fortresses from the Dutch colonial period is based on the aim of informing the current condition of a number of these forts. In addition, it will also discuss the potential contained in it. Through this presentation, it is hoped that an overview of the steps that should be taken in endeavoring to preserve and (later) the use that might be applied to these fortresses is expected.